The central star of planetary nebula PHR 1315 − 6555 and its host Galactic open cluster AL 1. Issue 3 (5th February 2019) - Fragkou, V; Parker, Q A; Zijlstra, A; Shaw, R; Lykou, F
ABSTRACT: PHR 1315 − 6555 is a rare case of a Galactic planetary nebula that is a proven member of the open cluster AL 1. This membership allows its distance to be defined with precision, and thus accurate measurements of its physical characteristics along with the parameters of its central star (CS) can be obtained. In this work, we use the Hubble Space Telescope to detect this unique CS and constrain the cluster's physical parameters. Our results suggest that the cluster is at a distance of ∼12 kpc, is highly reddened, and has an age of about 0.66 Gyr and a turn-off mass of ∼2.2 M_ . Our deep colour–magnitude diagram suggests that the metallicity of the cluster is subsolar ( Z = 0.006). Our photometric measurements indicate that the planetary nebula's core is a faint blue star close to the nebular apparent centre, with an observed dereddened visual VEGA magnitude of 21.82 ± 0.60. A significant contribution from any possible binary companion is unlikely but possible. Our results show that the CS has an effective Zanstra temperature of about 113 kK and a mass of 0.58 M_, providing a unique additional point in the fundamental white dwarf initial-to-final-mass relationship.